2014
DOI: 10.2174/0929867321666131228203513
|View full text |Cite
|
Sign up to set email alerts
|

Drp1 in Ischemic Neuronal Death: An Unusual Suspect

Abstract: Mitochondria play a crucial role in multitude of cellular processes including energy production, calcium signaling, and apoptosis. This remarkable organelle constantly undergoes a complex cycle of fusion and fission, a crucial quality control system for maintaining homeostasis of the cell. Any impairment in this dynamic behavior is linked to a wide range of cellular abnormalities. Consistent with this concept, neuronal apoptosis often emanates in conjunction with rampant mitochondrial fragmentation. The mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…It is noteworthy that previous studies have indicated that hypothermia and Drp1 inhibition both have similar beneficial effects such as reduction of mitochondrial membrane potential (MMP), calcium mobilization, ROS production, cytochrome c release and caspase activation (Gong et al, 2013;Grohm et al, 2012;Zhao et al, 2005). Some studies have reported that hypothermia reduced expression of p53 (Zhang et al, 2010), which is able to upregulate Drp1 expression at both mRNA and protein levels (Pradeep et al, 2014). In addition, hypothermia reduced Bax expression (Wu and Wang, 2011), which are proapoptotic proteins of Bcl-2 family and triggers for Drp1 activation (Pradeep et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noteworthy that previous studies have indicated that hypothermia and Drp1 inhibition both have similar beneficial effects such as reduction of mitochondrial membrane potential (MMP), calcium mobilization, ROS production, cytochrome c release and caspase activation (Gong et al, 2013;Grohm et al, 2012;Zhao et al, 2005). Some studies have reported that hypothermia reduced expression of p53 (Zhang et al, 2010), which is able to upregulate Drp1 expression at both mRNA and protein levels (Pradeep et al, 2014). In addition, hypothermia reduced Bax expression (Wu and Wang, 2011), which are proapoptotic proteins of Bcl-2 family and triggers for Drp1 activation (Pradeep et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that hypothermia reduced expression of p53 (Zhang et al, 2010), which is able to upregulate Drp1 expression at both mRNA and protein levels (Pradeep et al, 2014). In addition, hypothermia reduced Bax expression (Wu and Wang, 2011), which are proapoptotic proteins of Bcl-2 family and triggers for Drp1 activation (Pradeep et al, 2014). So could hypothermia might inhibit Drp1 partially through hypothermia-reduced P53/Bax pathway?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings support the hypothesis that a mitochondrial mechanism may underlie the sex differences in long-term neurobehavioral outcome observed following HI. Mitochondrial fission (or fragmentation) (Pradeep et al, 2014; Zhang et al, 2015; Owens et al, 2015a) and autophagy (Weis et al, 2014; Li et al, 2015; Yu et al, 2015) are known to occur following cerebral ischemia–reperfusion injury. It is hypothesized that mitochondrial fragmentation segregates oxidatively modified mitochondrial proteins for elimination via mitochondrial-specific autophagy (mitophagy) (Twig et al, 2008; Soubannier et al, 2012; Norton et al, 2014).…”
Section: Introductionmentioning
confidence: 99%